Power and pleasure court life under King John, 1199-1216 - Thomas, Hugh M. ca. 20./21. Jh (Oxford scholarship online, 2020)
Although King John is remembered for his political and military failures, he also resided over a magnificent court. This text uses records of his reign to reconstruct his life at court, and explore how it produced both pleasure and soft power for the king.